2010
DOI: 10.1021/jm101116s
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Synthesis of 2-{2-Fluoro (or Bromo)-4-[(2-oxocyclopentyl)methyl]phenyl}propanoic Acid: Nonsteroidal Anti-inflammatory Drugs with Low Membrane Permeabilizing and Gastric Lesion-Producing Activities

Abstract: We previously proposed that membrane permeabilization activity of NSAIDs is involved in NSAID-induced gastric lesions. We here synthesized derivatives of loxoprofen that have lower membrane permeabilization activity than other NSAIDs. Compared to loxoprofen, the derivatives 10a and 10b have lower membrane permeabilization activity and their oral administration produced fewer gastric lesions but showed an equivalent anti-inflammatory effect. These results suggest that 10a and 10b are likely to be therapeuticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…a Data from our previous report. 25 in vitro observation that the inhibitory effect of 1 on COX-2 was indistinguishable from that of 31 (Table 2). The inhibitory activity of 31 on COX-2 was much higher than that of 23 (Table 2), indicating the importance of the modification position of the phenyl ring (3-or 2-position) for determining the inhibitory effect on COX-2.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…a Data from our previous report. 25 in vitro observation that the inhibitory effect of 1 on COX-2 was indistinguishable from that of 31 (Table 2). The inhibitory activity of 31 on COX-2 was much higher than that of 23 (Table 2), indicating the importance of the modification position of the phenyl ring (3-or 2-position) for determining the inhibitory effect on COX-2.…”
Section: Resultsmentioning
confidence: 92%
“…Synthesis of loxoprofen derivatives with modification at the 2-position of the phenyl ring by a para-substituted aryl group (24)(25)(26)(27)(28)(29)(30)(31)(32)(33) rings. We previously reported that two of the compounds, 2-fluoroloxoprofen 4a and 2-bromoloxoprofen 4b (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations